The Effects of the Biceps Brachii and Brachioradialis on Elbow Flexor Muscle Strength and Spasticity in Stroke Patients - Binbin Yu; Xintong Zhang; Yihui Cheng; Lingling Liu; null YanJiang; Jiayue Wang; Xiao Lu (Neural Plasticity)
Objective. Muscle weakness and spasticity are common consequences of stroke, leading to a decrease in physical activity. The effective implementation of precision rehabilitation requires detailed rehabilitation evaluation. We aimed to analyze the surface electromyography (sEMG) signal features of elbow flexor muscle (biceps brachii and brachioradialis) spasticity in maximum voluntary isometric contraction (MVIC) and fast passive extension (FPE) in stroke patients and to explore the main muscle groups that affect the active movement and spasticity of the elbow flexor muscles to provide an objective reference for optimizing stroke rehabilitation. Methods. Fifteen patients with elbow flexor spasticity after stroke were enrolled in this study. sEMG signals of the paretic and nonparetic elbow flexor muscles (biceps and brachioradialis) were detected during MVIC and FPE, and root mean square (RMS) values were calculated. The RMS values (mean and peak) of the biceps and brachioradialis were compared between the paretic and nonparetic sides. Additionally, the correlation between the manual muscle test (MMT) score and the RMS values (mean and peak) of the paretic elbow flexors during MVIC was analyzed, and the correlation between the modified Ashworth scale (MAS) score and the RMS values (mean and peak) of the paretic elbow flexors during FPE was analyzed. Results. During MVIC exercise, the RMS values (mean and peak) of the biceps and brachioradialis on the paretic side were significantly lower than those on the nonparetic side (p<0.01), and the RMS values (mean and peak) of the bilateral biceps were significantly higher than those of the brachioradialis (p<0.01). The MMT score was positively correlated with the mean and peak RMS values of the paretic biceps and brachioradialis (r=0.89, r=0.91, r=0.82, r=0.85; p<0.001). During FPE exercise, the RMS values (mean and peak) of the biceps and brachioradialis on the paretic side were significantly higher than those on the nonparetic side (p<0.01), and the RMS values (mean and peak) of the brachioradialis on the paretic side were significantly higher than those of the biceps (p<0.01). TheMAS score was positively correlated with the mean RMS of the paretic biceps and brachioradialis (r=0.62, p=0.021; r=0.74, p=0.004), and the MAS score was positively correlated with the peak RMS of the paretic brachioradialis (r=0.59, p=0.029) but had no significant correlation with the peak RMS of the paretic biceps (r=0.49, p>0.05). Conclusions. The results confirm that the biceps is a vital muscle in active elbow flexion and that the brachioradialis plays an important role in elbow flexor spasticity, suggesting that the biceps should be the focus of muscle strength training of the elbow flexors and that the role of the brachioradialis should not be ignored in the treatment of elbow flexor spasticity. This study also confirmed the application value of sEMG in the objective assessment of individual muscle strength and spasticity in stroke patients.